2014
DOI: 10.3109/14397595.2014.924194
|View full text |Cite
|
Sign up to set email alerts
|

Validation and additional support for an experimental animal model of fibromyalgia

Abstract: Our results show that ICS is a useful animal model to assess hypothesis about underlying mechanisms involved in the development of fibromyalgia as well as to evaluate possible future therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The UF was isolated from GSO (1 Kg, Naturgreen, Murcia, Spain) following conventional procedures and its components were analysed following the IUPAC method and described in Montserrat-de la Paz et al 7 In brief, GSO was saponified at 80ºC by refluxing with 50 ml of 2 N potassium hydroxide solution in ethanol (Panreac, Barcelona, Spain), boiling gently until the solution became clear and then for additional 20 min. Heating was stopped by addition of 50 ml distillate water through the top of the condenser and the solution was Table 1).…”
Section: Isolation and Chemical Characterization Of Unsaponifiable Frmentioning
confidence: 99%
See 2 more Smart Citations
“…The UF was isolated from GSO (1 Kg, Naturgreen, Murcia, Spain) following conventional procedures and its components were analysed following the IUPAC method and described in Montserrat-de la Paz et al 7 In brief, GSO was saponified at 80ºC by refluxing with 50 ml of 2 N potassium hydroxide solution in ethanol (Panreac, Barcelona, Spain), boiling gently until the solution became clear and then for additional 20 min. Heating was stopped by addition of 50 ml distillate water through the top of the condenser and the solution was Table 1).…”
Section: Isolation and Chemical Characterization Of Unsaponifiable Frmentioning
confidence: 99%
“…MTT-formazan crystals were solubilized with DMSO (Sigma), and then measured with a microplate reader at 570 nm corrected to 650 nm. 15 Cell survival was expressed as the percentage of absorbance compared with that obtained in control, non-treated cells.…”
Section: Cell Viability Assay (Mtt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fibromyalgia (FM) is characterized by generalized tenderness in ≥11 of 18 tender points (1) and chronic widespread pain that lasts >3 months (2). Mechanical hyperalgesia is a common symptom of FM (3), which is a painful syndrome of largely unknown etiology and pathology that is often accompanied by various phenomena. In addition, emerging evidence has indicated that pain amplification within the central nervous system serves an important role in the pathology of FM-associated pain (4), which is associated with numerous other symptoms (5).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of this painful syndrome include fatigue (6), anxiety (7), sleep disturbance (8), temporomandibular disease and depression (9). An animal model of FM must include widespread pain and associated symptoms of fatigue and psychological disturbance (3).…”
Section: Introductionmentioning
confidence: 99%